2021
DOI: 10.1177/15347346211040593
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Pomegranate Seed Oil on Healing in a Rat Wound Model With Antioxidant, Vascular, and Histopathological Parameters

Abstract: The study aimed to evaluate the efficiency of pomegranate ( Punica granatum) seed oil in wound healing in excised rats. Sixteen female young Wistar Albino Rats weighing approximately 300 to 320 g were randomly divided into 2 groups as the treatment (=pomegranate seed oil group) and control groups in this experiment. Six different wounds 1 cm apart from the midline and each other were formed with a 6 mm punch biopsy instrument. Three wounds were left open (open wound group) whereas 3 wounds were sutured with 4/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The increased rate of wound contraction, lesser epithelialization phase, and lesser scar area led to faster healing as confirmed by the increased healed area compared to (untreated) control. The wound healing results of the present study are in agreement with those reported in literature; topical application of grape seed extract [25,26] or pomegranate seed extract [27,28] on excision wounds in animals exhibited a significant (p ˂0.001) diminishing in wound area compared to untreated wounds, in addition to accelerated wound closure rate in Vitis vinifera and Punica granatum seed extracts-treated wounds.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increased rate of wound contraction, lesser epithelialization phase, and lesser scar area led to faster healing as confirmed by the increased healed area compared to (untreated) control. The wound healing results of the present study are in agreement with those reported in literature; topical application of grape seed extract [25,26] or pomegranate seed extract [27,28] on excision wounds in animals exhibited a significant (p ˂0.001) diminishing in wound area compared to untreated wounds, in addition to accelerated wound closure rate in Vitis vinifera and Punica granatum seed extracts-treated wounds.…”
Section: Discussionsupporting
confidence: 92%
“…Topical treatment with these extracts also resulted in a higher production of vessel enclosure growth factor (VEGF) at the edge of the wound. Altogether, the topical application of this extract facilitated skin wound healing [28,32].…”
Section: Discussionmentioning
confidence: 89%
“…Treatment parameters were evaluated through in vivo experiments involving the application of PSO to post-excision wounds in rats once daily for 14 days. The findings indicate that PSO partially aids in treating excision wounds in rats and may be suitable for clinical treatment in humans, albeit requiring large-scale controlled studies ( Atsü Md et al, 2023 ). Furthermore, an effective dental scaffold, crafted with PSE, pomegranate peel extract (PPE), polyvinyl alcohol, and starch using 3D printing technology, has been developed for treating periodontal disease.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Pomegranate has a wide variety of different types of bioactive compounds, is native to the nations of the Mediterranean region, and may be consumed in the form of the fruit itself as juice, flower extract, seed oil, roots, leaves, or peel [14]. It contains polyphenols, flavonoids, anthocyanin, ascorbic acid, ellagic acid, carotenoids, tannins, and other compounds [15].…”
Section: Introductionmentioning
confidence: 99%